Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Experience the convenience of getting reliable answers to your questions from a vast network of knowledgeable experts. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Answer:
[tex]x=6[/tex]
Step-by-step explanation:
We want to solve the equation:
[tex]\displaystyle \log_6(2x-6)+\log_6x=2[/tex]
Recall the property:
[tex]\displaystyle \log_bx+\log_by=\log_b(xy)[/tex]
Hence:
[tex]\log_6(x(2x-6))=2[/tex]
Next, recall that by the definition of logarithms:
[tex]\displaystyle \log_b(a)=c\text{ if and only if } b^c=a[/tex]
Therefore:
[tex]6^2=x(2x-6)[/tex]
Solve for x. Simplify and distribute:
[tex]36=2x^2-6x[/tex]
We can divide both sides by two:
[tex]x^2-3x=18[/tex]
Subtract 18 from both sides:
[tex]x^2-3x-18=0[/tex]
Factor:
[tex](x-6)(x+3)=0[/tex]
Zero Product Property:
[tex]x-6=0\text{ or } x+3=0[/tex]
Solve for each case. Hence:
[tex]x=6\text{ or } x=-3[/tex]
Next, we must check the solutions for extraneous solutions. To do so, we can simply substitute the solutions back into the original equations and examine its validity.
Checking x = 6:
[tex]\displaystyle \begin{aligned} \log_{6}(2(6)-6)+\log_{6}6&\stackrel{?}{=} 2 \\ \\ \log_6(12-6)+(1)&\stackrel{?}{=}2 \\ \\ \log_6(6)+1&\stackrel{?}{=}2 \\ \\ 1+1=2&\stackrel{\checkmark}{=}2\end{aligned}[/tex]
Hence, x = 6 is indeed a solution.
Checking x = -3:
[tex]\displaystyle\begin{aligned} \log_6(2(-3)-6) + \underbrace{\log_6-3}_{\text{und.}} &\stackrel{?}{=} 2\\ \\ \end{aligned}[/tex]
Since the second term is undefined, x = -3 is not a solution.
Therefore, our only solution is x = 6.
Answer:
x = 6
Step-by-step explanation:
The given logarithmic equation is ,
[tex]\implies log_{6}(2x - 6) + log_{6}x = 2[/tex]
We can notice that the bases of both logarithm is same . So we can use a property of log as ,
[tex]\bf \to log_a b + log_a c = log_a {( ac)} [/tex]
So we can simplify the LHS and write it as ,
[tex]\implies log_{6} \{ x ( 2x - 6 )\} = 2 [/tex]
Now simplify out x(2x - 6 ) . We get ,
[tex]\implies log_6 ( 2x^2 - 6x ) = 2 [/tex]
Again , we know that ,
[tex]\bf \to log_a b = c , a^c = b [/tex]
Using this we have ,
[tex]\implies 2x^2 - 6x = 6^2 \\\\\implies 2x^2 - 6x -36 = 0 [/tex]
Now simplify the quadratic equation ,
[tex]\implies x^2 - 3x - 18 = 0 \\\\\implies x^2 -6x + 3x -18=0\\\\\implies x( x -6) +3( x - 6 ) = 0 \\\\\implies (x-6)(x+3) = 0 \\\\\implies x = 6 , -3 [/tex]
Since logarithms are not defined for negative numbers or zero , therefore ,
[tex]\implies 2x - 6 > 0 \\\\\implies x > 3 [/tex]
Therefore the equation is not defined at x = -3 . Hence the possible value of x is 6 .
[tex]\implies \underline{\underline{ x \quad = \quad 6 }}[/tex]
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.